Selected Intangible Factors Of Regional Development: An Analysis Of Spatial Relationships - Dańska-Borsiak, Barbara; Laskowska, Iwona (Comparative Economic Research. Central and Eastern Europe, 2014)
As spatial diversity of economic development is one of the main problems of modern economies, researchers have attempted to define the conditions and factors influencing this phenomenon. Among others, two intangible factors are suggested: human capital and social capital (Herbst ed. 2007). The primary objective of this work is a spatial and spatio-temporal analysis of the diversification of human and social capital within the Polish NUTS 3 subregions. The two detailed targets are constructing composite indicator of both of the mentioned types of capital as well as examining spatial interactions between human capital, social capital and the GNP level per capita. The large diversification of human and social capital in the Polish subregions has been confirmed. Clusters of regions with low levels of human capital have been indicated, whereas in the case of social capital a grouping of its high values was observed. The research also confirmed the positive correlation between GNP per capita and human capital, with high values of both variables in the larget cities. Additionally, there are some subregions with high levels of economic development surrounded by low levels of human and social capital (Łódź, Szczecin, Wrocław). It is possible that high level of GNPpc in these regions was the incentive causing the relocation of human capital from the neighbouring regions. The correlation between GNPpc and social capital, where significant, is of the low-high type. These subregions are located in the east and south of Poland.